Quantitative risk assessment and interventional recommendations for preventing canine distemper virus infection in captive tigers at selected wildlife stations in Thailand - Kanittha Tonchiangsai; Anuwat Wiratsudakul; Suwicha Kasemsuwan; Ruangrat Buddhirongawatr; Weerapong Thanapongtharm; Kan Kledmanee; Tatiyanuch Chamsai; Nareerat Sangkachai; Bencharong Sangkharak; Pakpoom Aramsirirujiwet; Sarin Suwanpakdee (PLoS ONE, 2025)
Canine distemper virus (CDV) can cause high morbidity and mortality in large felids and pose a significant threat to the conservation of captive and non-captive tiger (Panthera tigris). This study conducted in Thailand’s wildlife stations aimed to assess the risks of CDV introduction to captive tiger populations. A stochastic quantitative risk assessment model was employed to determine the pathways and estimate the risk probabilities through humans, animal reservoirs, and fomites. The final risk probability of entry, obtained from a combination of six entry pathways, indicated that the absence of measures resulted in a relatively high risk at 0.858. The sensitivity analysis identified CDV-contaminated human hands, followed by other CDV-infected wild animals, and CDV-contaminated equipment, as the most influential pathways of CDV spread. Risk probabilities were compared among those without intervention, with routine intervention at wildlife stations, and with full intervention implementation. Implementing all interventions at the captive wildlife stations significantly reduced the risk of CDV introduction. These interventions included control measures such as quarantining and isolating infected animals and providing treatment to reduce infectiousness. Preventive measures included screening tests for healthy individuals for early detection of asymptomatic or pre-symptomatic cases, preventing further spread or complications, CDV vaccination campaigns, and promoting hand hygiene among staff and visitors. Environmental interventions involve restricting dogs and cats from accessing tiger enclosures, disinfecting animal transport vehicles, using separate equipment for each cage, etc. Together, these interventions lowered the median risk of CDV introduction to 0.089, representing an 89.6% risk reduction. This approach assessed CDV infection risks and adapted interventions to specific situations at wildlife stations. Consistent implementation of these measures is essential to minimize CDV spread. Wildlife stations must strictly implement these interventions as standard procedures to protect the health of captive tigers.